Family Life Education: Translational Family Science in Action. Issue 4 (12th December 2017) - Darling, Carol A.; Cassidy, Dawn; Rehm, Marsha
Abstract : Translational family science lies at the intersection of family research and the practice of family life education (FLE). Discussion of the foundational principles of FLE (education, prevention, strengths‐based, and research and theory‐based) and its key components (culture, context, content, and practice) provide a framework for considering the reciprocal relationship between family science and family life education in the context of translational family science. Further discussion is provided regarding possible barriers to progress and the need to better integrate discovery science and practice science.